1993
DOI: 10.3109/08880019309029508
|View full text |Cite
|
Sign up to set email alerts
|

Oral Megadose Methylprednisolone Versus Intravenous Immunoglobulin for Acute Childhood Idiopathic Thrombocytopenic Purpura

Abstract: Twenty children with acute idiopathic thrombocytopenic purpura (ITP) were randomized to receive either oral megadose methylprednisolone (MDMP) or intravenous immunoglobulin G (IV IgG). Normal platelet counts (> or = 150 x 10(9)/l) were obtained in 6 patients of each group in 3 days and in 8 and 9 patients treated with oral MDMP and with IV IgG within 1 week, respectively. It is concluded that oral MDMP could easily be used for the early elevation of platelet counts, which is important for ITP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…In our analysis, children with ITP initially treated with IVIG were more likely to have platelet counts ‡150 · 10 9 /l and ‡50 · 10 9 /l at 6 months from diagnosis than children initially receiving no or other drug treatment. Among studies involving randomization between corticosteroids and IVIG and with a follow-up of at least 6 months, none have demonstrated a significant long-term effect in favour of IVIG treatment (Imbach et al, 1985;Blanchette et al, 1993Blanchette et al, , 1994Ozsoylu et al, 1993;Albayrak et al, 1994;Fujisawa et al, 2000;Ancona et al, 2002;Duru et al, 2002;Erduran et al, 2003). However, a recent meta-analysis of these nine studies (Imbach et al, 1985;Blanchette et al, 1993Blanchette et al, , 1994Ozsoylu et al, 1993;Albayrak et al, 1994;Fujisawa et al, 2000;Ancona et al, 2002;Duru et al, 2002;Erduran et al, 2003) found a statistically significant beneficial effect of IVIG 6 months after diagnosis (Beck et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, children with ITP initially treated with IVIG were more likely to have platelet counts ‡150 · 10 9 /l and ‡50 · 10 9 /l at 6 months from diagnosis than children initially receiving no or other drug treatment. Among studies involving randomization between corticosteroids and IVIG and with a follow-up of at least 6 months, none have demonstrated a significant long-term effect in favour of IVIG treatment (Imbach et al, 1985;Blanchette et al, 1993Blanchette et al, , 1994Ozsoylu et al, 1993;Albayrak et al, 1994;Fujisawa et al, 2000;Ancona et al, 2002;Duru et al, 2002;Erduran et al, 2003). However, a recent meta-analysis of these nine studies (Imbach et al, 1985;Blanchette et al, 1993Blanchette et al, , 1994Ozsoylu et al, 1993;Albayrak et al, 1994;Fujisawa et al, 2000;Ancona et al, 2002;Duru et al, 2002;Erduran et al, 2003) found a statistically significant beneficial effect of IVIG 6 months after diagnosis (Beck et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…198 High-dose methylprednisolone. HDMP (given as an oral 7-day course of 30 mg/kg/d for 3 days followed by 20 mg/kg/d for 4 days) has been used as an alternative to IVIg [200][201][202] (evidence level Ib-III).…”
Section: Treatment Options For Children With Persistent or Chronic Itpmentioning
confidence: 99%
“…In acute ITP , treatment options include corticosteroids, IVIG and anti-D IgG and thrombocyte suspension in conditions where bleeding can not be stopped or in case of urgent surgical intervention (1,23,38,(39)(40)(41)(42)(43)(44). In recent years, interferon, monoclonal antibodies (rituksimab) and helycobacter treatment have also been tried (38).…”
Section: Treatment Of Acute Childhood Itpmentioning
confidence: 99%